Dental applications of Punica granatum L. in the treatment of gingivitis: A review of ethnomedicinal uses, randomized clinical trials, and antibacterial potential against Porphyromonas gingivalis - Lima Bezerra, José Jailson; Domingos da Silva, Jadson Mathyas [UNESP] (Elsevier, 2025)
Ethnopharmacological relevance: Mouthwashes based on medicinal plants have demonstrated benefits in controlling plaque and inflammation, acting positively on the oral hygiene of patients with gingivitis. In traditional medicine, Punica granatum L. has been used to treat oral diseases in countries in Europe, Asia, North America, and Africa. Aim of the study: The present study aimed to conduct a comprehensive review on the dental applications of Punica granatum L. for the treatment of gingivitis, including ethnomedicinal uses, analysis of randomized clinical trials, antibacterial activity against Porphyromonas gingivalis, mechanisms of action of phytochemicals isolated from this plant, and preclinical toxicity. Materials and methods: The literature was retrieved from Google Scholar, PubMed®, SciELO, and ScienceDirect®, since the first report published on the topic in 2001 until March 2024. Results: Several clinical trials have demonstrated that mouthwashes containing P. granatum have equal or better efficacy than chlorhexidine in treating patients with gingivitis, confirming the indications for use of this plant by traditional communities. However, reports on the in vitro antibacterial activity of extracts from the fruits of this plant have not shown clinical relevance against the pathogen P. gingivalis. The ellagitannin punicalagin isolated from P. granatum has shown potential against several strains of Gram-positive and Gram-negative bacteria, but, to date, this compound has not yet been tested against P. gingivalis. It is likely that the mechanisms of action of flavonoids, such as quercetin, are involved in the inhibition of the activities of the RgpA, RgpB, and Kgp proteases of P. gingivalis. Conclusions: In summary, natural products obtained from P. granatum do not present toxic side effects and can be considered as possible substitutes of commercial products recommended for the treatment of gingivitis and other oral diseases.
Keywords: Mechanism of action; Medicinal plant; Mouthwashes; Natural products; Periodontal disease; Pomegranate